O BRINQUEDO E A BRINCADEIRA: CRIANÇAS EM DIFERENTES CONTEXTOS HISTÓRICOS (GUARAPUAVA-PR): 1950-2006 - Gartner, Giselle Priscila Scheidt Martins (2019)
This research aimed to discuss the similarities and differences of many issues, such as gender, consumption and freedom regarding culturally developed expressions manifested through play. For data collection, it was established an oral history methodology, which was based on a semi-structured interview, as well as the analysis of photographic records containing toys and games taken in Guarapuava-PR between 1950 and 2006. The main items chosen to be approached were dolls, strollers and freestyle outdoor activities, forming a set of constitutive elements, which despite being in constant reconstruction, continue to walk side by side with childhood and its conception of child. Considering that childhood and play change over time and with different social, economic and geographical contexts, this study was based on authors such as Gilles Brougère, Tizuko Morchida Kishimoto and Walter Benjamin. In this context, significant differences were found with regards to the physical space and time allocated to these activities. Besides that, the craft construction and imagination, previously essential to play, today ends up yielding to the standardization of objects and their technology. And even with such pertinent studies, these are still insufficiently discussed in the academic and social environment, which ends up hindering the realization of effective and pertinent attitudes to the need to play, even though this is essential for human development.